Nursing leadership : a concise encyclopedia - Feldman, Harriet R. (Springer Pub., 2008)
''We are delighted to introduce this book to a new generation of readers. The challenges in nursing, as well as in health care, have never been greater. The need for resources such as this text is profound.''. --from the foreword by Joanne Disch, PhD, RN, FAAN, Professor and Lillehei Chair in Nursing Leadership and Director, Katharine J. Densford International Center for Nursing Leadership, School of Nursing, University of Minnesota, and Kathleen Dracup, DNSc, FNP, RN, FAAN, Dean and Chair of Nursing Education, School of Nursing, University of California, San Francisco. The Concise Encyclopedi.